A Journal of Three Months' Walk in Persia in 1884 by Captain John Compton Pyne Introduction, Notes and Translation - Harris, Russell; Afsharian, Marjan (Iranian Studies Series, 2017)
A primary source on a journey to Persia by Captain John Compton Pyne in 1884 revealing the West's fascination with the Middle East in Victorian times. The book includes an introduction by the editors and a transcription of the manuscript with notes and the original illustrations, mainly watercolours. An important historical document and eye-witness account pertaining to Iran, anthropology, area studies, study of 'orientalism' and colonialism, and for historians.